VCAM-1 Expression in Endometerium with Human Cytomegalovirus Infection - Al-Obaidi, Asmaa B; Habib, Manal Adnan; Al-Zuhairy, Shatha (AL-Kindy College Medical Journal, 2012)
Background: To elucidate the possible role of human cytomegalovirus in pregnancy loss through induction of certain pro-inflammatory adhesion molecules. Methods: Paraffin embedded sections of curate samples were obtained from 34 women had spontaneous abortion, and 5 women had elective termination of pregnancy (as control), and then subjected for immunohistochemistry analysis to detect human cytomegalovirus (HCMV) early protein and VCAM-1 molecule. Results: Nine out of 34 women with spontaneous abortion were positive for HCMV early protein, with a significantly higher expression of VCAM-1 in HCMV positive cases as compared with HCMV negative and the control groups (p = 0.05, 0.001 respectively). Conclusion: HCMV infection may play an important role in the pathology of pregnancy loss on multidirectional bases include inducing the surface expression of pro-inflammatory adhesion molecules like VCAM-1.